MAINTENANCE - EQUIPMENT ANALYSIS OF BIOLOGICAL LABORATORY FACILITIES AND INFRASTRUCTURE AT SENIOR HIGH SCHOOL IN YOGYAKARTA - Yoan Dea Irawati; Zulfa Nabila Putri; Shafira Hanum Febriana; Ikhda Niami Fauziyatunnisa; Much. Fuad Saifuddin; Etika Dyah Puspitasari (ATRIUM PENDIDIKAN BIOLOGI, 2022)
Practicum activities can be carried out properly if laboratory facilities and infrastructure are available. The completeness of laboratory infrastructure can support achieving optimal activities. This study aim to determine completeness and maintenance of biology laboratory facilities and infrastructure in Yogyakarta. The type of research descriptive quantitative. This research was conducted at Senior High School in Yogyakarta, consisting 3 schools. Those schools were selected by random sampling. Respondents in this study included both head of the laboratory and laboratory assistant, data collection through observation and interview. The data were analyzed descriptively. The results show that School A 78% (very complete), School B 60% (complete) and School C 66% (complete). Maintenance of facilities and infrastructure in the laboratory of School A is well-maintained. In contrast, maintenance of laboratory biology facilities and infrastructure in School B and C are unkempt.